2013
DOI: 10.1186/1475-2840-12-31
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of haptoglobin polymorphisms with cardiovascular disease and type 2 diabetes in the diabetes heart study

Abstract: BackgroundHaptoglobin (HP) is an acute phase protein that binds to freely circulating hemoglobin. HP exists as two distinct forms, HP1 and HP2. The longer HP2 form has been associated with cardiovascular (CVD) events and mortality in individuals with type 2 diabetes (T2DM).MethodsThis study examined the association of HP genotypes with subclinical CVD, T2DM risk, and associated risk factors in a T2DM-enriched sample. Haptoglobin genotypes were determined in 1208 European Americans (EA) from 473 Diabetes Heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 37 publications
1
35
0
2
Order By: Relevance
“…Our study used a candidate gene approach, and an accompanying editorial (2) suggested that the recently completed genome wide association (GWA) studies of millions of single nucleotide polymorphisms (SNPs) should identify the same genetic predictor of CHD, to confirm our findings. However, the Hp CNV is not a SNP; it is a 1.7 kb replication, and as detailed in the following text, our investigations and the work of 2 different groups (3,4) show that currently available GWA studies cannot tag Hp CNV or identify the association between this variant and risk of disease.…”
mentioning
confidence: 62%
“…Our study used a candidate gene approach, and an accompanying editorial (2) suggested that the recently completed genome wide association (GWA) studies of millions of single nucleotide polymorphisms (SNPs) should identify the same genetic predictor of CHD, to confirm our findings. However, the Hp CNV is not a SNP; it is a 1.7 kb replication, and as detailed in the following text, our investigations and the work of 2 different groups (3,4) show that currently available GWA studies cannot tag Hp CNV or identify the association between this variant and risk of disease.…”
mentioning
confidence: 62%
“…Taken together, genetic studies strongly support the theory that high concentrations of TG-rich lipoproteins or remnant cholesterol are causal risk factors for cardiovascular disease and all-cause mortality [2, [131][132][133][134][135][136][137][138], and that low HDL cholesterol is probably an innocent bystander. Low HDL cholesterol might merely be a long-term marker of raised TG and remnant cholesterol.…”
Section: Tg and Hdlmentioning
confidence: 94%
“…Ten independent longitudinal studies have demonstrated that individuals homozygous for the Hp 2 allele (Hp 2-2 genotype), present in 36% of all DM individuals, have a several fold increased risk of atherothrombosis (i.e., myocardial infarction) in the setting of DM as compared to individuals without the Hp 2-2 genotype and DM [1221]. We have proposed that this Hp genotype and CVD interaction may be due to Hp genotype differences in the response to intraplaque hemorrhage and in the ability to protect against extracorpuscular Hb in the atherosclerotic plaque [2226].…”
mentioning
confidence: 99%